Language Styles in UFC Trash Talk : a Sociolinguistics Study - Faizi Noor Muhammad; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This research explores how fighters in the Ultimate Fighting Championship (UFC) use language in their press conferences and media appearances, with a focus on the styles and purposes of their verbal exchanges. Using a qualitative approach, the study looks at transcripts from UFC events between 2010 and 2025, especially the words of well-known fighters such as Conor McGregor, Nate Diaz and other Fighters. The analysis is based on Labov’s (1972) framework for storytelling, which includes parts like the abstract, orientation, complicating action, evaluation, resolution, and coda, as well as Jakobson’s (1960) ideas about the different functions of language. The research identifies three main ways fighters use language: confrontational, which involves direct insults and threats; humorous, which includes sarcasm and irony; and performative, which is more about making a dramatic or showy statement. Out of 20 data of UFC trash talk, the analysis revealed that fighters strategically employ various language styles to construct their public personas, intimidate opponents, and engage audiences. Regarding language style classification, the data shows a relatively balanced distribution across narrative categories. Orientation, Complicating Action, and Evaluation were the most frequently used styles, each (20%) of the analyzed data, abstract and Coda each accounted for (15%), resolution appeared least frequently with only (10%). This research contributes to to sociolinguistics, particularly in understanding how language is strategically used in sports media discourse. It highlights how trash talk functions as a context-dependent communicative practice shaped by social norms, performance, and interactional goals